Chromosome and Linear Plasmid Sequences of a 2015 Human Isolate of the Tick-Borne Relapsing Fever Spirochete, Borrelia turicatae - Kingry, Luke C. (Genome Announc, 2016)
The sequences of the complete linear chromosome and 7 linear plasmids of the relapsing fever spirochete Borrelia turicatae are presented in this report. The 925,547 bp of chromosome and 380,211 bp of plasmid sequence were predicted to contain a total of 1,131 open reading frames, with an average G+C content of 29.7%.